2-(4-Chloro-anilino)pyridine - Fairuz, M. Zainal Abidin; Aiyub, Zaharah; Abdullah, Zanariah; Ng, Seik Weng (International Union of Crystallography, 2008)
The two aromatic rings of each of the four independent molecules in the asymmetric unit of the title compound, C(11)H(9)ClN(2), are approximately coplanar; the four mol-ecules are arranged into two amino-pyridyl N-H⋯N hydrogen-bonded pairs. The structure has a 15% twin component related by a twofold rotation about [100].